2018
DOI: 10.3171/2017.1.jns162046
|View full text |Cite
|
Sign up to set email alerts
|

Improved operative efficiency using a real-time MRI-guided stereotactic platform for laser amygdalohippocampotomy

Abstract: OBJECTIVE MR-guided laser interstitial thermal therapy (MRgLITT) is a minimally invasive method for thermal destruction of benign or malignant tissue that has been used for selective amygdalohippocampal ablation for the treatment of temporal lobe epilepsy. The authors report their initial experience adopting a real-time MRI-guided stereotactic platform that allows for completion of the entire procedure in the MRI suite. METHODS Between October 2014 and May 2016, 17 patients with mesial temporal sclerosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In 2 patients who required ablation of both the rostrum and splenium of the corpus callosum, we performed LITT entirely in the MRI suite using the ClearPoint platform (MRI Interventions). 13 Briefly, these patients were transported to the MRI suite for induction of general anesthesia. Next, they were positioned laterally with the right side up in the ClearPoint 4-point fixation head frame.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In 2 patients who required ablation of both the rostrum and splenium of the corpus callosum, we performed LITT entirely in the MRI suite using the ClearPoint platform (MRI Interventions). 13 Briefly, these patients were transported to the MRI suite for induction of general anesthesia. Next, they were positioned laterally with the right side up in the ClearPoint 4-point fixation head frame.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…This series of procedures is possible through local anesthesia and light sedation, although most centers perform this procedure under general anesthesia. Recently, some authors have reported experience on MRgLITT in epilepsy patients using the ClearPoint ® system (MRI Interventions, Inc., Irvine, CA, USA) that allows for the entire surgical procedure to be performed utilizing real-time MR guidance in the MR imaging suite by providing a frameless stereotactic platform [14,26,38]. This MR-guided frameless stereotactic platform is more time-efficient, reducing the mean anesthesia time by more than 100 minutes.…”
Section: Mr-guided Laser Ablation Systemmentioning
confidence: 99%
“…Alternatively, with recent advances, it is possible to perform the entire procedure within the MRI suite using a real-time MRI system, such as the ClearPoint platform, for neuronavigation. 6 The ClearPoint platform consists of a MRI-compatible percutaneous SMART-frame, a hand-held twist drill, ceramic stylet, and a trajectory guide tower. Use of the platform obviates the need for skull fiducial markers or a stereotactic computed tomography scan.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging technologies have enabled increased operative efficiency for MRgLITT for SLAH. Ho et al 6 reported on utilizing a real-time MRI platform for completion of the entire procedure in the MRI suite. Rapid adoption of this new platform for MRgLITT was intuitive and led to decreased case times across the board, with preservation of accuracy and minimal learning curve.…”
Section: Mtlementioning
confidence: 99%
See 1 more Smart Citation